Pengaruh Pupuk Organik Cair Limbah Tomat (Solanum lycopersicum L.) dan Daun Lamtoro (Leucaena leucocephala) Terhadap Pertumbuhan dan Hasil Tanaman Pakcoy (Brassica rapa L.) - Anisa Yardanova; Ruqoyyah Nasution; Sri Purwati; Zenia Lutfi Kurniawati (JURNAL VIGOR, 2026)
This study aimed to determine the effect of liquid organic fertilizer derived from tomato waste and leucaena leaves on the growth and yield of pakcoy plants. The study was conducted for 35 days at Jl. Perjuangan Unmul, Sempaja Selatan, Samarinda Utara, Samarinda City, East Kalimantan Province. This research employed a true experimental design using a Randomized Block Design (RBD) consisting of four treatments: K0 (control), P0 (20%), P1 (40%), and P2 (60%), with six replications. The data were analyzed using one-way analysis of variance. The results showed that the plant height of pakcoy at 14 days after planting (DAP) was identical across all treatments, measuring 4 cm; therefore, it was not subjected to statistical analysis. Similarly, the number of leaves at 14 DAP was relatively uniform, with an average of five leaves per plant. At 21, 28, and 35 DAP, the analysis of variance indicated that the treatments had a significant effect on plant height, with calculated F values of 30.82, 32.44, and 25.33, respectively, which exceeded the critical F value (3.10). The treatments also had a significant effect on the number of leaves at 21, 28, and 35 DAP, with calculated F values of 10.00, 27.35, and 21.28, respectively. In addition, a significant effect was observed on fresh weight at harvest, with a calculated F value of 133.66, which exceeded the critical F value (3.10). These findings indicate that the P1 treatment (40%) was the most effective concentration in enhancing the growth of pakcoy plants compared to the other treatments.